IoT blood pressure monitoring system - Norlezah Hashim; Nurbahirah Norddin; Fakrulradzi Idris; Siti Nur Ilmani Mohd Yusoff; Madiha Zahari (Institute of Advanced Engineering and Science, 2020)
The number of patients in hospital keep increasing every year and, some patients’s blood pressure must be measured by medical staff regularly. This means that the medical staff need to attend to the patient routinely and several readings are required in each session to make sure the results are accurate. Therefore, there is a need to simplify the monitoring process inside hospital in Malaysia. In this work, IoT blood pressure monitoring system (IBPMS) is designed to monitor patient’s blood pressure remotely. This project use Raspberry Pi as a gateway to view the value of blood pressure online. Result showed that the design is capable to transfer data from blood pressure detector through the network using USB TTL serial cable which is directly attached to the Raspberry Pi. User can also view the blood pressure reading continuously from Telegram application and email service. Furthermore, the system can measure the value of blood pressure accurately when user is in sitting position.